2021
DOI: 10.1186/s12905-021-01374-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of premenstrual syndrome and its association with psychosocial and lifestyle variables: a cross-sectional study from Palestine

Abstract: Background Premenstrual Syndrome (PMS) is a very common problem with symptoms that can negatively affect normal daily life. This cross-sectional study aimed to investigate the prevalence of PMS symptoms and their relationship with psychosocial status and lifestyle of female students at An-Najah National University in Palestine. A sample of 398 female students was randomly selected to participate in the study. Arabic Premenstrual Scale (A-PMS) was used for PMS assessment. Psychosocial variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 18 publications
(30 reference statements)
4
24
0
Order By: Relevance
“…Both studies revealed that females with PMS exhibited more symptoms of depression, anxiety, and stress. Moreover, a couple of recent studies conducted among university female students also showed that increased PMS severity is associated with a worsening of depression, anxiety, and stress symptoms [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Both studies revealed that females with PMS exhibited more symptoms of depression, anxiety, and stress. Moreover, a couple of recent studies conducted among university female students also showed that increased PMS severity is associated with a worsening of depression, anxiety, and stress symptoms [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Skin blemish, which was the most prevalent symptom in our study, may occur when sebum secretion increases due to increased progesterone secretion after ovulation. However, the prevalence rate of the skin disorder for university students varies greatly from 36% in Iran (Ghiasi, Keramat, & Mollaahmadi, 2018) to 80% for acne in Palestine (Abu Alwafa, Badrasawi, & Haj Hamad, 2021). Moreover, 56% of adults in USA reported that their acne got worse before menstruation (Geller, Rosen, Frankel, & Goldenberg, 2014), and 44% of adult women experienced premenstrual flares of their acne but this was not affected by ethnicity (Stoll et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Epidemiological data shows that the symptoms are often mild in 75% of the women, but 3–8% reported to experience moderate to severe symptoms that are associated with substantial distress and functional impairment. 7 Premenstrual symptoms often interferes with occupational productivity, quality of life, interpersonal relationships and daily living activities and also it is considered as an limiting factor for female adolescents and young women aspiring to achieve developmental goals. Studies have also shown that adolescents with PMS are in poor health 8 and in some women it is so bad that they are unable to cope up with their daily lifestyle with PMS.…”
Section: Introductionmentioning
confidence: 99%